2020
DOI: 10.1007/jhep03(2020)068
|View full text |Cite
|
Sign up to set email alerts
|

Universal 3d Cardy block and black hole entropy

Abstract: We discuss the Cardy limit of 3d supersymmetric partition functions which allow the factorization into the hemisphere indices: the generalized superconformal index, the refined topologically twisted index and the squashed sphere partition function. In the Cardy limit, the hemisphere index can be evaluated by the saddle point approximation where there exists a dominant saddle point contribution, which we call the Cardy block. The Cardy block turns out to be a simple but powerful object as it is a building block… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 83 publications
6
69
0
1
Order By: Relevance
“…We comment in passing that a relation analogous to (3.13) has been shown to hold in 3d, relating the large N superconformal index, Z S 2 ω ×S 1 , in the Cardy-like limit |ω| 1, to the squashed S 3 partition function in the interesting paper [69]. The results discussed here, and the holographic arguments in [12], suggest that at large N the 3d relation may hold in an extended regime as well.…”
Section: A Large N Cardy Formulasupporting
confidence: 51%
“…We comment in passing that a relation analogous to (3.13) has been shown to hold in 3d, relating the large N superconformal index, Z S 2 ω ×S 1 , in the Cardy-like limit |ω| 1, to the squashed S 3 partition function in the interesting paper [69]. The results discussed here, and the holographic arguments in [12], suggest that at large N the 3d relation may hold in an extended regime as well.…”
Section: A Large N Cardy Formulasupporting
confidence: 51%
“…Solutions of this type have been studied in [54] and it will be very interesting to generalize them, understand their relation to the Lorentzian rotating black hole solutions in [55,56], and establish their dual field theory description. It is important also to study the relation between black saddles and the "gravitational blocks" discussed recently in [57,58]. We also note that it will be interesting to construct black saddle solutions which correspond to general values of the parameter n = 1 which specifies the R-symmetry chemical potential in (2.2) and understand their interpretation in the dual field theory.…”
Section: Generalizations and Open Questionsmentioning
confidence: 84%
“…As a related matter, it had been believed that the superconformal index could not capture the entropy of BPS black holes in the dual AdS space due to the severe boson/fermion cancellation. However, inspired by the extremization principle found in [19][20][21], it has been recently observed that the superconformal index can actually reproduce the entropy of supersymmetric black holes in AdS 4 [22][23][24], AdS 5 [25][26][27], AdS 6 [28], and AdS 7 [26]. The primary breakthrough was allowing the chemical potentials to be complex to obstruct (−1) F cancellation [29].…”
Section: Introductionmentioning
confidence: 99%